Benefits of home care for children with advanced cancer - Kiriaki, Panagiota; Saridi, Maria (Health & Research Journal, 2017)
Introduction: It is considered that the home nursing care is better than the hospital care for a child with cancer because of the fact that the environment of a hospital may provoke a kind of psycho-emotional burden. Aim: The purpose of this review was to investigate literature which concerns the hospital care of pediatric patients with advanced cancer and the size of psycho-emotional burden on these children. Materials and methods: The data search was made in international databases for the period 2000-2015 and in earlier typical studies which signal the beginning of home care for children with cancer. Results: Pediatric patients receiving home health care are vulnerable groups of the population with specific and unique needs. Home care for children with life-threatening diseases is a process which aims to provide quality of life to both children and their family. This holistic care involves not only the biological needs of the pediatric patient but also concerns their mental, social and spiritual needs. Pediatric nurses, as well as other health professionals, that deal with such cases should convey positive energy and love to the children except from just possessing knowledge. Psychotherapy and drug treatment are the two main intervening approaches in children with depression symptoms. The most important support resource during child cancer care is the family environment. Good communication between family members is the first step that will help them cope with the child’s disease. Conclusion: Given that home care is superior to all other types of care, pediatric cancer patients being treated in their home receive the best possible care in aspects of meeting their biological, psychological, social and spiritual needs.